2020
DOI: 10.1055/s-0039-1697024
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic Postoperative Spinal Epidural Hematoma after Spinal Decompression Surgery: Prevalence, Risk Factors, and Functional Outcome

Abstract: Objective Postoperative spinal epidural hematoma (pSEH) with symptomatic compression of nervous structures after spinal decompression surgery is a rare complication. Delayed evacuation may result in severe neurologic impairment. We present a large single-center analysis of the prevalence, potential risk factors, and functional recovery after pSEH. Methods A retrospective review of our institutional database of spinal decompression surgery over 15 years yielded 6,024 consecutive patients. A total of 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
71
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(72 citation statements)
references
References 34 publications
(38 reference statements)
1
71
0
Order By: Relevance
“…With regard to initial symptoms, our study was consistent with previous ndings that lumbar PSEH often leads to paralysis and pain [1,15]. In our study, muscle weakness was the most common symptoms regardless of the time of onset, following the dysesthesias and pain.…”
Section: Clinical Featuressupporting
confidence: 92%
See 2 more Smart Citations
“…With regard to initial symptoms, our study was consistent with previous ndings that lumbar PSEH often leads to paralysis and pain [1,15]. In our study, muscle weakness was the most common symptoms regardless of the time of onset, following the dysesthesias and pain.…”
Section: Clinical Featuressupporting
confidence: 92%
“…Another risk factors that is found to be independent associated with delayed onset PSEH is previous spinal surgery at the same level. Many previous studies investigated the role of this factor in PSEH [1,4,17]. However, only one study identi ed it as a risk factor [17].…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Delamarter et al [4] demonstrated in a study on dogs that when compressions to the spinal cord last for 6 h, there are no neurological recovery and progressive spinal cord necrosis. Other studies indicate that if patients with an acute spinal cord compression have had surgical decompressions within 8 h, their neurological functions will make good or partial recovery [5,6]. A timely diagnosis and urgent management of neurologic complications are very important when helping patients recover from neurological deficits after lumbar spine surgeries.…”
Section: Discussionmentioning
confidence: 99%
“…[4] demonstrated in a study on dogs that when compressions to the spinal cord last for six hours, there is no neurological recovery and progressive spinal cord necrosis. Other studies indicate that if patients with an acute spinal cord compression have had surgical decompressions within eight hours, their nerurological functions will make good or partial recovery [5,6] . A timely diagnosis and urgent management of neurologic complications are very important when helping patients recover from neurological deficits after lumbar spine surgeries.…”
Section: Patient Factorsmentioning
confidence: 99%